High‐Efficiency ITO‐Free Organic Photovoltaics with Superior Flexibility and Upscalability. Issue 17 (25th March 2022) - Zheng, Xiangjun; Zuo, Lijian; Zhao, Feng; Li, Yaokai; Chen, Tianyi; Shan, Shiqi; Yan, Kangrong; Pan, Youwen; Xu, Bowei; Li, Chang‐Zhi; Shi, Minmin; Hou, Jianhui; et al.
Abstract: Developing indium‐tin‐oxide (ITO)‐free flexible organic photovoltaics (OPVs) with upscaling capacity is of great significance for practical applications of OPVs. Unfortunately, the efficiencies of the corresponding devices lag far behind those of ITO‐based rigid small‐area counterparts. To address this issue, an advanced device configuration is designed and fabricated featuring a top‐illuminated structure with ultrathin Ag as the transparent electrode. First, a conjugated polyelectrolyte layer, i.e., PCP‐Li, is inserted to effectively connect the bottom Ag anode and the hole transport layer, achieving good photon to electron conversion. Second, charge collecting grids are deposited to suppress the increased resistance loss with the upscaling of the device area, realizing almost full retention of device efficiency from 0.06 to 1 cm 2 . Third, the designed device delivers the best efficiency of 15.56% with the area of 1 cm 2 on polyimide substrate, representing as the record among the ITO‐free, large‐area, flexible OPVs. Interestingly, the device exhibits no degradation after 100 000 bending cycles with a radius of 4 mm, which is the best result for flexible OPVs. This work provides insight into device structure design and optimization for OPVs with high efficiency, low cost, superior flexibility, and upscaling capacity, indicating the potential for the future commercialization of OPVs. Abstract : A high‐performance indium‐tin‐oxide‐free organic photovoltaic (OPV) with superior flexibility and upscaling capacity is demonstrated. The OPV device adopts a top‐illuminated structure optimized by an anode buffer layer and charge collecting grid, and delivers a record efficiency of 15.56%. Moreover, the flexible OPV exhibits no degradation after 100 000 bending cycles with a radius of 4 mm, which represents the best result for flexible OPVs.